2014
DOI: 10.1007/s11554-014-0417-y
|View full text |Cite
|
Sign up to set email alerts
|

Real time motion estimation using a neural architecture implemented on GPUs

Abstract: This work describes a neural network based architecture that represents and estimates object motion in videos. This architecture addresses multiple computer vision tasks such as image segmentation, object representation or characterization, motion analysis and tracking. The use of a neural network architecture allows for the simultaneous estimation of global and local motion and the representation of deformable objects. This architecture also avoids the problem of finding corresponding features while tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…C++). Finally, the use of parallel programming techniques can further reduce the computation time of the proposed methodology [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…C++). Finally, the use of parallel programming techniques can further reduce the computation time of the proposed methodology [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Further details of the image processing aspects of the surveillance system can be found in our previous work [10]. Furthermore, in [35], a comparison with other tracking and motion estimation methods can be found that demonstrates the accuracy of the system with a single camera.…”
Section: Gng-seqmentioning
confidence: 91%
“…This application does not necessarily require a temporal component, as it can analyze video frames as images. However, some of the other applications in video do require a temporal component, including motion detection [383], [572], [1768], [1769], [2632], motion estimation [1031], [1704], [2633], motion tracking [905], [917], [2634], [2635], and activity recognition [916], [2636].…”
Section: Applicationsmentioning
confidence: 99%